Carbon emission reduction effect of China's final demand structure change from 2013 to 2020: a scenario-based analysis. Issue 4 (4th July 2019) - Deng, Mingjun; Zhong, Shihu; Xiang, Guocheng
Abstract: This study employs scenario analysis to measure the carbon emissions reduction potential of the final demand structure changes in China from 2013 to 2020. The results indicate that under the business as usual (BAU) scenario (i.e. in which China's final demand structure, energy structure and technical level in 2020 are the same as those in 2012), China's gross domestic product of 2020 calculated by 2005 constant price is 6, 427, 658, 783×10, 000 yuan and China's total carbon emissions will reach 1, 531, 692.29×10, 000 tons, with its carbon emission intensity standing at 2.3686 t/10, 000 yuan (it is only 25.57% lower than in 2005). Furthermore, under the specific final demand product structure (when "government consumption", "export consumption", "residents' consumption + capital formation" accounts for 12%, 18% and 70%of final demand, respectively), China's total carbon emissions in 2020 will be reduced by between 167, 595.33×10, 000 and 204, 142.45×10, 000 tons compared to the BAU scenario, and carbon emission intensity nationwide will be reduced by 33.71-35.49% compared with 2005. Finally, based on the assumptions and conclusions, this study puts forward some suggestions to realize the China's carbon emission reduction commitments.